O ensino de administração pública: histórico e diagnóstico: reflexões sobre a formação do administrador - Andrade, Rui Otávio Bernardes de (1995)
This Dissertation discusses the importance of the improvement of the quality of teaching in Higher Education Schools, mainIy those devoted to the Public Administration formation and its reIation to the services rendered by Government institutions. It reports the difficulties imposed to the educational system by the Portuguese Crown at that time, and the Iater efforts by the Republican Government aiming at the creation of Management Schools. It aIso deaIs with the politicaI difficulties and misunderstandings that had to be overcome so that the existence of a new professional of management could formally be accepted in the market pIace. This dissertation aIso discusses the present educational process of Administrator formation, anaIysing the pedagogical means and techniques regarding the course under way. It aIs o takes the ethicaI formation of Public Administrators into consideration, suggesting new paradigms of efficiency and effectiveness in the public services. Finally, it discusses the rôle of the University vis à vis the scientific community and the introduction of new technological solutions able to lead to a new didactic-pedagogicallevel. This new knowledge should be connected to the solution of social demands.